A Rent Extraction View of Employee Discounts and Benefits - Marino, Anthony M.; Zábojník, Ján (Journal of Labor Economics, 2008)
We examine how firms can use employee discounts and perks to extract information rents from employees who have private information about their preferences and outside opportunities. The firm creates different bundles of the perk and salary in response to different employee characteristics and marginal costs of the perk. Strategic bundling can lead firms to provide perks even without a cost advantage over the outside market and to deviate from the marginal cost pricing. We characterize how optimal perk provision depends on the set of feasible contracts, on the perk’s marginal cost, and on the perk’s price in the outside market.